Burkina Faso : Staff Report for the Second Review Under the Poverty Redaction and Growth Facility. (IMF Staff Country Reports; Country Report, 2001)
Burkina Faso recorded a solid economic performance in 1996-99, with sustained real GDP growth in the 5-6 percent range, subdued inflation, an improved fiscal position, and progress in liberalizing the economy. Monetary policy is conducted at the regional level by the Central Bank of West African States. The objective of the fiscal policy is to strengthen the budgetary position in order to remain within original program parameters. The authorities will implement a transparent and automatic pricing policy for petroleum products.